2002
DOI: 10.1021/ma0121464
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Polystyrene from Narrow Disperse Polymer Particles by Surface-Initiated Atom Transfer Radical Polymerization

Abstract: Grafting of polystyrene from narrow disperse polymer particles by surface-initiated atom transfer radical polymerization was investigated. Poly(DVB80) particles prepared by precipitation polymerization were used as starting particles. Their residual surface vinyl groups were hydrochlorinated to form chloroethylbenzene initiating sites for subsequent ATRP of styrene using CuBr/2bipy as catalyst system. Polystyrene was found grafted not only from the particle surfaces but also from within a thin shell layer, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 38 publications
3
98
0
1
Order By: Relevance
“…9 The microspheres also have a thin surface layer consisting of lightly crosslinked and swellable poly(DVB). 10 Both DVB containing 55% (DVB55) and 80% (DVB80) can be employed for the synthesis of microspheres; DVB55 results in microspheres with a slightly thicker, lightly crosslinked surface layer than DVB80 because of the lower content of DVB in DVB55.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The microspheres also have a thin surface layer consisting of lightly crosslinked and swellable poly(DVB). 10 Both DVB containing 55% (DVB55) and 80% (DVB80) can be employed for the synthesis of microspheres; DVB55 results in microspheres with a slightly thicker, lightly crosslinked surface layer than DVB80 because of the lower content of DVB in DVB55.…”
Section: Introductionmentioning
confidence: 99%
“…10,14,15 The novel approach employs ultraviolet (UV) irradiation to initiate the polymeri-zation (k ¼ 365 nm) at ambient temperatures. The critical advantage of the present UV based approach is the fact that the particle formation process is performed at ambient temperature (25 8C T 40 8C), thus making it a highly valuable tool for the use in controlled drug release technology (e.g., the encapsulation of proteins during particle synthesis) which typically requires low temperatures (T < 37 8C) to avoid protein/ biomolecule denaturation.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported grafting using surface-initiated living radical polymerization (LRP) on a variety of surfaces, e.g., inorganic solid surfaces [29][30][31] and organic polymer surfaces. [32][33][34] Most of these studies are focused on the control of molecular weight of the grafted polymer, while only limited attention has been given the quantification of grafting densities. However, Fukuda and coworkers [35,36] concentrated on the quantification of grafting densities as well as attempts to achieve high grafting densities on solid substrates.…”
mentioning
confidence: 99%
“…Two steps are typically needed to obtain core-shell particles such as in grafting by living radical polymerization techniques, two-stage precipitation polymerization, and stepwise saponification of suspension and dispersion polymerization. [22][23][24][25][26][27][28][29] Of particular interest is the surface modification of spheres with poly(ethylene glycol) (PEG) to generate surfaces that are biocompatible, and resistant to attacks by macrophages and other blood components in the human body. Furthermore, PEGylated spheres are observed to have a decreased protein adsorption.…”
Section: Full Papermentioning
confidence: 99%